Preparation method of lead-based halloysite-loaded composite heat stabilizer

The lead-based halloysite composite heat stabilizer addresses dispersibility and migration issues in PVC products by loading lead ions into halloysite nanotubes and modifying them with coupling agents, enhancing thermal stability and transparency.

CN119119586AActive Publication Date: 2024-12-13QINGDAO AMOS RESOURCE & TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411174956.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-13
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

Existing lead salt stabilizers for PVC materials suffer from poor dispersibility, compatibility, and migration issues, affecting the transparency and environmental safety of PVC products.

Method used

A method for preparing a lead-based halloysite composite heat stabilizer involves acid etching and hydrothermal treatment of halloysite nanotubes to load lead ions, followed by organic modification with coupling agents and compounding with phosphite and epoxy compounds to enhance dispersibility and compatibility with PVC resin.

Benefits of technology

The composite stabilizer improves thermal stability, reduces lead ion migration, and maintains transparency in PVC products, offering better processing usability and environmental safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005010466880000111
    Figure BDA0005010466880000111
  • Figure BDA0005010466880000121
    Figure BDA0005010466880000121
Patent Text Reader

Abstract

The invention relates to a preparation method of a lead-based loaded halloysite composite stabilizer, and belongs to the technical field of heat stabilizer preparation, and the key point of the technical scheme is that the preparation method comprises the following steps: S1, preparing a precursor; step S2, synthesizing lead-based loaded halloysite; step S3, organic modification of lead-loaded halloysite; s4, preparing a composite heat stabilizer; the prepared composite heat stabilizer has excellent heat stability, has good dispersity and compatibility with PVC resin, and is not prone to migration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat stabilizer preparation, and in particular to a method for preparing a lead-based loaded halloysite composite heat stabilizer. Background Art

[0002] Polyvinyl chloride (PVC) is the second largest general-purpose plastic after polyethylene (PE) in terms of output. It has the advantages of high strength, corrosion resistance, flame resistance, good insulation, high transparency, etc. It is widely used in industrial construction, agriculture, daily necessities, packaging, electricity, public utilities, etc. However, PVC products are easy to degrade during processing and molding. If it is not inhibited, the physical properties of the products will be greatly reduced or even lose their use value. Heat stabilizers can effectively inhibit its degradation.

[0003] Lead salt stabilizers are the most commonly used heat stabilizers for PVC materials. They can effectively improve the thermal stability of PVC materials, especially the long-term thermal stability. They are also inexpensive and have long occupied more than 70% of the market share of PVC heat stabilizers. Commonly used lead salt stabilizers include tribasic lead sulfate, dibasic lead phosphite, etc. Lead salt stabilizers have poor dispersibility and poor compatibility with PVC resins. In the preparation of transparent products, they will seriously affect the transparency of the material. In the application of soft PVC products such as cable materials, due to the use of a large amount of plasticizers, lead salt stabilizers are very easy to migrate to the surface of the product and thus harm the environment. Summary of the invention

[0004] The invention aims to provide a method for preparing a lead-based halloysite-loaded composite heat stabilizer. The composite heat stabilizer prepared by the method has good thermal stability, good dispersibility and compatibility with PVC resin, and is not easy to migrate.

[0005] The above technical purpose of the invention is achieved through the following technical scheme: a preparation method of a lead-based loaded halloysite composite thermal stabilizer, comprising the following method steps:

[0006] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring fully, reacting for 1-3 hours, separating the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is (5-30):1;

[0007] Step S2, synthesizing lead-based loaded halloysite, adding a precursor to a hydrothermal synthesis reactor, and then adding a lead nitrate solution to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:(1-10); introducing an inert gas into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:(1-10); reacting at 120-200° C. for 3-5 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0008] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C.-160° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0009] The mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and coupling agent is 10:(1-3):(1-3):(2-5);

[0010] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy compound, and polyol according to a mass ratio of 10: (0.5-2): (0.5-1.5): (0.5-2), and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0011] Preferably, in step S1, the selected halloysite has an outer diameter of 20-60 nm, an inner diameter of 5-20 nm, and a length of 300-3000 nm.

[0012] Preferably, the coupling agent is any one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.

[0013] Preferably, in step S3, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and titanate coupling agent is 10:1.5:1.5:3.

[0014] Preferably, the epoxy compound is any one or more of epoxy soybean oil, epoxy linseed oil, epoxy butyl stearate, and epoxy octyl stearate.

[0015] Preferably, the polyol is any one or more of pentaerythritol, dipentaerythritol, polyvinyl alcohol, tetrahydroxymethylcyclohexanol, ditrimethylolpropane, carbitol, sorbitol, mannitol, xylitol and maltitol.

[0016] Preferably, in step S4, the mass fraction ratio of modified lead-loaded halloysite, phosphite, epoxy compound and polyol is 10:1:1:5.

[0017] In summary, the present invention includes at least one of the following beneficial technical effects:

[0018] 1. The present invention subjects natural halloysite nanotubes to acid etching treatment, so that the aluminum oxide layer on the inner surface of the natural halloysite nanotubes is partially removed, which significantly increases the inner tube cavity space and active sites of the halloysite nanotubes, and improves their adsorption and loading capacity for lead metal ions; at the same time, combined with hydrothermal treatment, soluble lead ions are loaded into the halloysite precursor tubes under alkaline conditions, so that the soluble free lead is deposited and anchored on the inner surface of the halloysite nanotubes, thereby blocking the free migration hazard of the lead base; on the other hand, due to the nanoscale size structure of the selected matrix halloysite nanotubes, the loaded lead-based elements are dispersed at the nanoscale, which greatly improves the stabilizer efficiency of the lead base.

[0019] 2. The present invention utilizes the abundant hydroxyl groups on the outer surface of halloysite nanotubes to carry out graft cross-linking reaction with PVC resin under the action of coupling agents, etc., thereby improving the dispersibility and compatibility of lead-based loaded halloysite in PVC resin and inhibiting its migration to the surface of PVC resin.

[0020] 3. The present invention utilizes the synergistic effect principle of composite stabilizers to composite auxiliary heat stabilizers such as phosphites with modified lead-loaded halloysite, thereby further improving its dynamic and static thermal stability and processing usability during PVC processing. DETAILED DESCRIPTION

[0021] In order to more clearly illustrate the present invention, the invention is further described in detail below in conjunction with the embodiments. It should be understood by those skilled in the art that the following description is an explanation of the invention content, not a limitation, and therefore, the protection scope of the present invention should not be limited thereto.

[0022] Example

[0023] Example 1

[0024] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0025] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0026] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0027] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0028] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0029] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0030] Example 2

[0031] The only difference between Example 2 and Example 1 is that in step S3, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1.5:1.5:3.

[0032] Example 3

[0033] The only difference between Example 3 and Example 1 is that in step S3, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:3:3:5.

[0034] Example 4

[0035] The only difference between Example 4 and Example 1 is that, in step S4, the modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol are compounded in a mass ratio of 10:1:1:1.5.

[0036] Example 5

[0037] The only difference between Example 5 and Example 1 is that in step S4, the modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol are compounded in a mass ratio of 10:2:1.5:2.

[0038] Example 6

[0039] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0040] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 2 hours, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0041] Step S2, synthesizing lead-based loaded halloysite, adding a precursor to a hydrothermal synthesis reactor, and then adding a lead nitrate solution to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 120° C. for 4 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0042] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0043] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0044] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0045] Example 7

[0046] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0047] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring fully, reacting for 3 hours, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 5:1;

[0048] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:10; reacting at 120° C. for 5 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0049] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0050] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0051] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0052] Example 8

[0053] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0054] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0055] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 160° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0056] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 140° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0057] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0058] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0059] Example 9

[0060] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0061] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0062] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 200° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0063] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 160° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0064] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0065] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0066] Example 10

[0067] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0068] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring fully, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 15:1;

[0069] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:5; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0070] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0071] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0072] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0073] Embodiment 11

[0074] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0075] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring fully, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 5:1;

[0076] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:10; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0077] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0078] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0079] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0080] Example 12

[0081] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0082] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0083] Step S2, synthesizing lead-based loaded halloysite, adding a precursor to a hydrothermal synthesis reactor, and then adding a lead nitrate solution to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:1; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0084] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0085] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent is 10:1:1:2;

[0086] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0087] Embodiment 13

[0088] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0089] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0090] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0091] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0092] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and titanate coupling agent is 10:1:1:2;

[0093] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy linseed oil, and polyvinyl alcohol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based halloysite-loaded composite heat stabilizer.

[0094] Embodiment 14

[0095] A method for preparing a lead-based loaded halloysite composite thermal stabilizer comprises the following steps:

[0096] Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring sufficiently, reacting for 1 hour, separating out the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is 30:1;

[0097] Step S2, synthesizing lead-based loaded halloysite, adding a precursor into a hydrothermal synthesis reactor, and then adding a lead nitrate solution into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:10; introducing nitrogen into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise into the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:1; reacting at 120° C. for 3 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain lead-loaded halloysite;

[0098] Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and silane coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite;

[0099] Among them, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and phosphate coupling agent is 10:1:1:2;

[0100] Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy butyl stearate, and sorbitol in a mass ratio of 10:0.5:0.5:0.5, and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

[0101] Test methods

[0102] PVC material sample preparation

[0103] The heat stabilizer samples prepared in Examples 1-14 and the control heat stabilizer were made into PVC samples according to the following method:

[0104] The following raw materials were weighed according to mass fraction: 100 parts of PVC resin particles, 3 parts of heat stabilizer, 30 parts of dioctyl phthalate, and 0.3 parts of stearic acid;

[0105] After the raw materials are blended, they are added to a double-roll mill, mixed at 170-185°C for 2-5 minutes, and then pressed using a fully automatic hot press at 170-185°C and 100-110 bar for 1 minute to obtain a PVC product. The sample is cut into square sheets with a thickness of 2±0.02mm and a width of 10±0.1cm for later use.

[0106] The control heat stabilizers are selected as follows: Control Example 1 is tribasic lead sulfate; Control Example 2 is a composite stabilizer of tribasic lead sulfate and dibasic lead phosphite in a mass ratio of 2:1.

[0107] The PVC samples prepared from the heat stabilizer samples of Examples 1-14 were marked as test samples 1-14, respectively.

[0108] The PVC samples prepared from the heat stabilizer samples of Control Examples 1-2 were marked as Control Samples 1-2, respectively.

[0109] PVC material sample performance test

[0110] Test samples 1-14 and control samples 1-2 were tested for transparency performance, Congo red static thermal stability time, and lead ion concentration, respectively;

[0111] Among them, the transparency performance test is carried out according to the method specified in the national standard GB / T2410-2008;

[0112] The Congo red static thermal stability time test is carried out according to the method specified in GB 2917-1982.

[0113] The lead ion concentration test method is tested according to the following method:

[0114] Cut the sample into small particles with a side length of about 2mm, and put the PVC particles into a glass test tube with a diameter of 17mm and a length of 150mm, ensuring that the PVC material is about 2cm high in the test tube. Pour distilled water into the test tube to ensure that the liquid level is about 10cm high. After placing the filled test tube in a 60℃ water bath and heating for 12 hours, filter out the water and determine its lead ion concentration according to the standard method of GB7470-1987. The test results are detailed in Table 1.

[0115]

[0116]

[0117] Table 1 Test data of test samples 1-14 and control samples 1-2

[0118] In the experimental operation of Examples 1-14, the control variables such as the amount of raw materials, type, temperature, reaction time, etc. in the preparation process of the lead-based loaded halloysite composite thermal stabilizer were changed respectively, wherein Example 1-3 changed the amount ratio of the components of lead-loaded halloysite, stearic acid, maleate, and silane coupling agent in step S3; Examples 1, 4, and 5 changed the amount ratio of modified lead-loaded halloysite, phosphite, epoxy soybean oil, and pentaerythritol in step S4; Examples 1, 6, and 7 changed the reaction time of the precursor preparation and the lead-based loaded halloysite preparation; Examples 1, 8, and 9 changed the reaction temperature in the preparation process of lead-based loaded halloysite and modified lead-based loaded halloysite; Examples 1, 10, and 11 changed the amount of hydrochloric acid in the precursor preparation and the amount of sodium hydroxide in the preparation of lead-based loaded halloysite; Examples 1 and 12 changed the amount of lead nitrate in the preparation of lead-based loaded halloysite; Examples 1, 13, and 14 changed the types of coupling agent, epoxy compound, and polyol.

[0119] It can be seen from the test data in Table 1 that, compared with the traditional single lead salt stabilizer and the composite lead salt stabilizer, the lead-based loaded halloysite composite thermal stabilizer synthesized by the present invention has significantly improved the thermal stability of the PVC material when used in the PVC material system. In the Congo red static thermal stability time test, the Congo red time of the embodiment red can reach up to 51 minutes, and the Congo red time of the control example can reach up to 39 minutes, with an improvement of 30.8%.

[0120] In the application of transparent PVC materials, the light transmittance of the PVC sample using the composite heat stabilizer of the present invention is greatly improved compared with the PVC sample using the traditional lead salt stabilizer. This is because halloysite is a well-crystallized natural nanotube structure with active hydroxyl groups on the surface and between layers. The halloysite nanotube is used as the lead-based loading matrix to make the thermal stability action group reach the nanometer size, and through further organic modification, the halloysite has better compatibility and dispersibility in the PVC resin, thereby effectively reducing the effect of adding the heat stabilizer on the light transmittance of the PVC material system, so that the PVC product using the heat stabilizer of the present invention has good light transmittance compared with the PVC product adding the conventional heat stabilizer.

[0121] It can be seen from the data of the lead ion concentration test that the PVC material using the lead-based loaded halloysite composite heat stabilizer of the present invention has a significantly lower lead ion concentration in the sample infiltration liquid than the PVC material using the traditional lead salt stabilizer, and the lead ions are not easy to precipitate. This is because the high specific surface area and high adsorption capacity of the active points in the inner cavity of the halloysite nanotubes combined with the hydrothermal reaction make the lead element firmly deposited in the inner cavity of the halloysite nanotubes, and it is difficult to form free ions to escape from the halloysite nanotubes; and further, the lead-based loaded halloysite is modified by organic coating coupling, so that it is more stable in the PVC resin matrix.

[0122] In summary, the composite heat stabilizer prepared by the method of the present invention has good thermal stability when used in a PVC system compared with the existing lead salt heat stabilizer, and has good dispersibility and compatibility with PVC resin. The produced PVC product has better light transmittance, and lead ions are not easy to precipitate and migrate.

[0123] Although some specific embodiments of the invention have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the invention. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the invention. The scope of the invention is defined by the appended claims.

Claims

1. A method for preparing a lead-based loaded halloysite composite thermal stabilizer, characterized in that: The method comprises the following steps: Step S1, preparing a precursor, adding halloysite and a dilute hydrochloric acid solution into a reaction container, stirring fully, reacting for 1-3 hours, separating the solid in the reaction container, washing and drying to obtain a precursor; wherein the mass ratio of halloysite to the dilute hydrochloric acid solution is (5-30):1; Step S2, synthesizing lead-based loaded halloysite, adding a precursor to a hydrothermal synthesis reactor, and then adding a lead nitrate solution to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the lead nitrate is 100:(1-10); introducing an inert gas into the hydrothermal synthesis reactor to exhaust the air in the hydrothermal synthesis reactor, and then gradually adding a sodium hydroxide solution dropwise to the hydrothermal synthesis reactor, wherein the mass fraction ratio of the precursor to the sodium hydroxide is 400:(1-10); reacting at 120-200° C. for 3-5 hours, and then filtering and separating the solid reactant in the solution, washing and drying to obtain the lead-based loaded halloysite; Step S3, organic modification of lead-loaded halloysite, preheating the lead-loaded halloysite to 110° C.-160° C., then sequentially adding the lead-loaded halloysite, stearic acid, maleate, and coupling agent into a high-speed mixer, dispersing and stirring evenly, and standing to room temperature to obtain the modified lead-loaded halloysite; The mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and coupling agent is 10:(1-3):(1-3):(2-5); Step S4, preparing a composite heat stabilizer, compounding modified lead-loaded halloysite, phosphite, epoxy compound, and polyol according to a mass ratio of 10: (0.5-2): (0.5-1.5): (0.5-2), and mixing them evenly to obtain the lead-based loaded halloysite composite heat stabilizer.

2. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: In step S1, the selected halloysite has an outer diameter of 20-60 nm, an inner diameter of 5-20 nm, and a length of 300-3000 nm.

3. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: The coupling agent is any one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.

4. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: In step S3, the mass fraction ratio of lead-loaded halloysite, stearic acid, maleate, and coupling agent is 10:1.5:1.5:

3.

5. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: The epoxy compound is any one or more of epoxy soybean oil, epoxy linseed oil, epoxy butyl stearate, and epoxy octyl stearate.

6. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: The polyol is any one or more of pentaerythritol, dipentaerythritol, polyvinyl alcohol, tetrahydroxymethylcyclohexanol, ditrimethylolpropane, carbitol, sorbitol, mannitol, xylitol and maltitol.

7. The method for preparing a lead-based loaded halloysite composite thermal stabilizer according to claim 1, characterized in that: In step S4, the mass fraction ratio of modified lead-loaded halloysite, phosphite, epoxy compound, and polyol is 10:1:1:1.5.

Citation Information

Patent Citations

  • Preparation method of PVC (Polyvinyl Chloride) heat shrinkable film

    CN107828147A

  • Efficient, flame-retardant, smoke-suppressing and environmentally-friendly bifunctional assistant, and PVC-U material prepared from same

    CN110669259A

  • Silane coupling agent modified halloysite nanotube loaded antioxidant compound, polycarbonate composition and preparation method and application thereof

    CN114106417A

  • Calcium-zinc heat stabilizer for foaming soft PVC (polyvinyl chloride) and application of calcium-zinc heat stabilizer

    CN115947980A

  • A clay based NANO confined reactor

    IN201731043481A